EVALUATION OF ORGANOPHOSPHATE AND ORGANOCHLORINE PESTICIDES IN FIBROUS FEEDSTUFFS IN KIRFI LOCAL GOVERNMENT AREA, BAUCHI STATE - Muhammad, B.; Mai, H. M.; Sanusi, M.; Jama’a, N.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted to evaluate the chemical pesticide residual concentrations on six crop residues in Kirfi LGA of Bauchi State. The chemicals studied were Organochlorine and Organohposphate while the crop residues were groundnut haulms, cowpea hay, cowpea husk, sorghum chaff, millet chaff and rice straw. Samples were collected from six farming communities of Badara, Wanka, Kafin Iya, Beni Kwagal and Tubule. The samples were prepared and subjected to laboratory analysis to determine the residual concentrations of the pesticides. Data generated were subjected to analysis of variance and means were separated using Duncan’s Multiple Range Test (DMRT). Results obtained revealed that location has no influence on the mean concentrations of the two organic compounds (0.42 - 0.57mg/kg). Similarly, no significant difference was found on the overall concentration of the pesticides in the six locations used. However, a significant (P<0.001) difference was found among the 2 pesticides in the six locations with the higher value of 0.63mg/kg for organophosphate and 0.37mg/kg for organochlorine. Both the overall and mean concentrations of the 2 pesticides were significantly (P<0.001) affected within the six crop residues in the six locations with cowpea hay having the highest values (1.05mg/kg) followed by cowpea husk (0.65mg/kg) while the lowest values were obtained on rice straw. The study showed that location has no influence on the residual concentrations and among the six crop residues studied. Cowpea hay and husk contained higher concentrations of the 2 organic compounds. Based on the result of this study, farmers should be informed on the negative effects of these chemical pesticides on humans as well as farm animals’ health.